Zooplankton composition and abundance in Villareal Bay, Philippines - Rosillo, Sheila Anne M.; Yap-Dejeto, Leni G. (2024)
Villareal Bay is known for green mussel (Perna viridis) cultivation and is fringed by mangroves, which serve as nursery areas for marine organisms. Nutrients from these organisms makes the bay a suitable environment for zooplankton, which are key intermediaries between phytoplankton and life forms from higher trophic levels. The effects of environmental changes in the bay could be apparent in the composition and abundance of zooplankton. However, there are no studies on zooplankton in Villareal Bay. Thus, this paper serves as a baseline study that aims to assess the composition and abundance of the zooplankton community in Villareal Bay. Four liters of water samples were collected and were filtered through a 60-um sieve once a month from August 2023 to January 2024 from three stations: near-mangrove zone, mariculture zone, and open water with minimal disturbance. A total of 33 zooplankton taxa were identified, with Class Copepoda dominating the bay (3.3 x 10 raised to the power of 5 - 5.2 x 10 raised to the power of 5 indivs/m³). Copepod nauplii, calanoids, and cyclopoids were among the dominant copepod groups, with the former having the highest abundance ranging from 1.5x10 raised to the power of 5 - 2.6×10 raised to the power of 5 indivs/m³. Fifteen out of the 33 zooplankton groups exhibited strong correlations (spearman's rho -0.51 - 0.72) with the recorded physico-chemical parameters; transparency, temperature, pH, DO, current velocity, salinity, light intensity, depth, TSS, phosphate and nitrate concentrations of Villareal Bay, suggesting that these taxa are more sensitive to these environmental factors here. Furthermore, a significant difference (p-value 0.03) between the sampling stations was observed, particularly the zooplankton abundances between the station near the mangroves (5.1 x 10 raised to the power of 5 - 8.8 x 10 raised to the power of 5 indivs/m³) and the station with minimal anthropogenic disturbance (5.0×10 raised to the power of 5 - 5.2 x 10 raised to the power of 5 indivs/m³).
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.